2 - Is There One Science, Western Science? DOI: 10.4314/ad.v30i3.22227 - Okere, Theophilus (Africa Development, 2005)
All humans by nature desire to know and humans are distinguished from the rest of creation by the miracle of knowledge. If all cultures have developed their own forms of knowledge, the spectacular success of a certain form of knowledge, science, notably in the west, has frequently led to its being exclusively attributed to the west. Yet science remains only one of many forms of knowledge and the west only one of its producers. The success of the west has tended to marginalize other forms of knowledge and other contributions to knowledge and, thus to impoverish an otherwise potentially rich and complex world knowledge landscape. It has tended to inhibit or even prevent the development of a really universal, human-knowledge project. Its very success, due essentially to its sustained application to technology, has enabled the development of a false superiority over other forms of knowledge and a real power hegemony of the west over other peoples. The future of lasting peaceful co-existence in the world may depend, in part, on the emancipation of other knowledge modes and forms.